Factors Relating to Job Satisfaction of Secondary School Teachers in the District of Balakong - K. P. Samu, Amaranathan (1998)
The aim of the study was to determine factors related to job satisfaction among secondary school teachers in Balakong. Two secondary schools in Balakong area were involved in the study. They were Sekolah Menengah Cheras Perdana and Sekolah Menengah Perimbun. Respondents consists of two hundred and twenty-seven teachers. A modified version of the Job Descriptive Index questionnaire was used in the study. The questionnaire is divided into two parts. Part one of the questionnaire determined the biodata of the respondents. Part two of the questionnaire dealt with job satisfaction level. The aspect of job were divided into twelve elements. The data collected were analysed using SPSS programme (Statistical Package for Social Services). Frequencies, percentages, means, standard deviation, Eta and Point biserial (rpb) were obtained. The study showed that teachers in the Balakong area were dissatisfied withtheir job. They were dissatisfied in eleven of the elements related to job satisfaction. However they were satisfied with security provided by the job (mean = 3.2). There was a significant and strong relationship between personal life with working experience (Eta =.51, P <.01), age (Eta =.42, p <.01), sex (rpb =.43, P <.01) and salary (Eta =.31, P <.01). Among the elements of intrinsic factors, work itself showed the highest mean (mean = 2.5). The lowest mean was shown by promotion (mean = 1. 9). In the hygiene factors job security showed the highest mean (mean = 3.2) and co-worker showed the lowest mean (mean = 1.9). The study did not support Herzberg's view that job satisfaction was influenced by intrinsic factors and dissatisfaction by Hygiene factors. The study showed that both the factors did not influence the respondents job satisfaction level.